The Influence Of Brand Equity, Customer Relationship Marketing And Service Perfomance On Customer Loyalty - Setiawan, Zunan; Dharmawan, Donny; Judijanto, Loso; Launtu, Ansir; Endrawati, Titin (Universitas Dharma Wacana, 2024)
As a company that offers financial services, Bank NTB Syariah is always motivated by the importance of trust when doing its everyday duties. Bank NTB Syariah is dedicated to bringing new ideas and solutions to customers' financial activities while adhering to Sharia laws and customs. In the Islamic banking sector, superior service quality and brand equity are the keys to success. Islamic banks are currently placing a great deal of emphasis on their customer relationship marketing since a well-executed plan may foster customer pleasure and loyalty. At Bank NTB Syariah KCP Aikmel Lombok Timur, this study aims to determine the impact of customer loyalty on brand equity, customer relationship marketing, and service performance. This study employed quantitative methods based on correlation analysis. A total of 70 respondents were acquired by using incidental sampling procedures to obtain the sample. A number of tests, including the validity, realibility, classic assumption, linear regression, and coefficient of determination tests, were used to analyze the data using IBM SPSS version 21. According to the research findings, Bank NTB Syariah's customer loyalty is positively and significantly impacted by its brand equity, customer relationship marketing, and service performance. KCP Aikmel can be used as a reference when developing policies for the bank to ensure that its customer loyalty is high by continuing to maintain its brand equity, customer relationship marketing, and service performance.